Investigating reading habits and their impact on reading performance among Indian undergraduate students - Komal Kumar Napa; Rajkumar Govindarajan; Sathya Subramanian; Senthil Murugan Janakiraman; Nageswari Devana; Billa Manindhar (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study investigates the reading habits, genre preferences, and reading behaviors of undergraduate students and examines how these factors influence their reading performance. A total of 342 responses were directly collected from students through a structured questionnaire. Descriptive statistics revealed strong inclinations toward analytical genres such as mystery/thriller, science fiction, and true crime, while newspaper reading frequency remained low. Hypothesis testing showed no significant differences in reading scores across gender or academic departments. A significant positive correlation emerged between daily reading duration and newspaper reading frequency. Most notably, students who preferred analytical genres demonstrated significantly higher reading scores (Cohen’s d=1.36). Regression analysis further confirmed genre preference as the strongest predictor of reading performance. These findings highlight the importance of genre engagement and daily reading routines in enhancing reading comprehension and literacy development. The study offers meaningful implications for educators, curriculum designers, and reading intervention programs.